Commodities prices and critical parameters for macroeconomic performance: a CGE analysis for Argentina, Brazil and Chile - Chisari, Omar Osvaldo (2019)
We study the potential performance of Argentina, Chile and Brazil, following a reduction of prices of exports and imports of commodities. To that aim, we construct three CGE models based on the same analytical framework. The impact of low commodities prices depends on the share of exports in GDP, the share of exports of commodities in total exports, the import-intensity of manufactures and the share of labor in GDP. We find that Argentina is vulnerable to the reduction of prices of commodities because it is highly dependent on exports of agricultural commodities and/or their derivatives. Chile is vulnerable to price reductions of copper even though its economy is protected by a sound macroeconomic policy and because its economy is less labor-intensive than the others. Brazil would be the less affected by a generalized fall of commodities prices since its economy is more diversified.